PEMAHAMAN KONSEPTUAL SISWA DITINJAU DARI KEMAMPUAN REPRESENTASI MATEMATIS MATERI FUNGSI DI SMAN 8 PONTIANAK - Nuril Hidayah; Edy Yusmin; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe research aims to find out students’ conceptual understanding in terms of mathematical representation ability in the function subject matter at SMA Negeri 8 Pontianak. The method used in this research is descriptive research method, especially descriptive quantitative. Based on the data analysis obtained: (1) Students’ conceptual understanding of the function subject matter with the visual category ability representation is at the medium criteria; (2) Students’ conceptual understanding of the function subject matter with the symbolic category ability representation  is at the lowest criteria; (3) Students’ conceptual understanding of  the function subject matter with verbal category ability representation is at the low criteria.Therefore, it can be concluded that the students' conceptual understanding of the  function subject matter in the eleventh grade of SMA Negeri 8 Pontianak were varied, in which the visual representation ability was higher than the verbal representation ability and the symbolic representation ability.  Keywords:  Conceptual Understanding, Function, Mathematical Representation Ability